Using the theory of planned behaviour and prototype willingness model to target binge drinking in female undergraduate university students - Todd, J.; Mullan, Barbara (Pergamon, 2011)
The current study investigated whether binge drinking in female undergraduates could be reduced by the mere measurement effect (MME), and by altering binge drinker prototypes from the prototype willingness model (PWM). Whether willingness added to the theory of planned behaviour (TPB) was also explored. Female undergraduates aged 17–25 (N=122) were randomly allocated to a prototype manipulation, mere measurement, or control group, and completed two online questionnaires separated by 14–21 days. Controlling for past behaviour, MME group consumed less alcohol than the control group, and this effect was more extreme for those who previously consumed more alcohol. However, the prototype manipulation had no effect. The TPB variables were predictive of intentions and behaviour, but willingness was not. Despite limitations, the MME could be utilised to reduce binge drinking in female undergraduates. The TPB appears to model binge drinking in female undergraduates better than the PWM, implying that binge drinking can be a reasoned behaviour.